Clinicopathological spectrum of BCR-ABL-Negative myeloproliferative neoplasms with correlation with janus-associated kinase 2 mutation - Roopa Dixith; A Sara; Navatha Vangala; Shantveer G Uppin; Megha S Uppin; A MV R Narendra; Tara Roshni Paul (Indian Journal of Medical and Paediatric Oncology)
Background: Non chronic myelogenous leukemia (non-CML)/BCR-ABL-negative myeloproliferative neoplasms (MPNs) include essential thrombocythemia (ET), polycythemia vera (PV), and primary myelofibrosis (PMF) (apart from chronic neutrophilic leukemia and chronic eosinophilic leukemia, which are rare). They are uncommon clonal disorders of adults, with an incidence ranging from 0.5 to 3/100,000 persons, BCR-ABL negative, and characterized by the activation of Janus-associated kinase 2 (JAK2). Very few studies have been reported from India. Aims and Objectives: The aims and objectives of this study were to analyze the clinicopathological spectrum and to determine the frequency of JAK2 mutation in patients of non-CML/BCR-ABL negative MPNs. Materials and Methods: Clinical and morphological features and frequency of JAK2 mutation in patients with PV, ET, and PMF were studied at a tertiary care hospital. The material was retrieved from the hematopathology records and reviewed. Results: JAK2V617F mutation was found in 10 of 14 cases (71%) of MPNs, 100% in PV, 50% in ET, and 71% of idiopathic myelofibrosis. The presence of JAK2V617F mutation was associated with a higher hemoglobin level (P < 0.05), a higher TLC (P < 0.05), and higher age (P < 0.05). Results showed that there are morphologic differences, and megakaryocytic morphology represents a useful clue for the differential diagnosis of these three BCR-ABL-negative MPN subtypes. Conclusion: The JAK2 V617F mutation was detected in 71% of patients with MPN disorders. Peripheral blood mutation screening for JAK2 V617F should be incorporated into the initial evaluation of patients suspected to have MPNs. Differences in megakaryocytic morphology provide the histomorphological hallmark of BCR-ABL-negative MPN subtypes.